ASSESSMENT OF EXERCISE BARRIERS IN TYPE 2 DIABETES PATIENTS: A CROSS SECTIONAL STUDY PERFORMED AT GOVERNMENT DISTRICT HEAD QUARTERS HOSPITAL, UDHAGAMANDAM, THE NILGIRIS, TAMIL NADU, INDIA - RAJA D; VENKATA RAMANA DEVI T; Dr. ANAND VIJAYAKUMAR P.R (International Journal of Pharma and Bio Sciences, 2014)
The purpose of this study is to assess and rank gender wise barriers associated towards exercise among type 2 diabetes patients. A cross-sectional study was conducted from March 2012 to August 2012 in Government District Head quarters hospital – A secondary care hospital, Udhagamandalam, Nilgiris District, Tamil Nadu State, India. Patients were analyzed for barriers towards regular exercise. Data were obtained through questionnaire and personal interview. Motivational factors among regular exercisers were assessed. The results were analyzed using GraphPad Prism Version 6.02.This study was performed in 150 type 2 diabetes mellitus patients. The results of this study showed that the internal factors such as lack of interest, lack of time, tiredness, body pain, lack of awareness about the importance of regular exercise in controlling diabetes, age, fear of hypoglycaemia and external factors such as family commitment, lack of social support and bad weather contribute to exercise barriers. Also the factors like habituation and feel of comfort contribute to regular exercise. The regular exercise behaviour of most people with Type 2 Diabetes Mellitus patients in the Nilgiris district, Tamil Nadu State, India do not comply with guidelines. It is better late than never to start suitable individual diabetes management care plan to those subjects with an individual exercise regimen considering gender wise barriers.